2023
DOI: 10.3390/economies11030073
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between FDI Inflows and Export Performance: An Empirical Investigation by Considering Structural Breaks

Abstract: The present study examines the relationship between FDI inflows and export performance in Bangladesh by considering the issue of structural breaks utilizing annual time-series data from 1972 to 2019. In the study, unit root tests were conducted without (ADF test and PP test) and with (ZA test and LP test) the presence of probable structural breaks in the dataset. A Johansen test of co-integration was employed to determine whether the variables were co-integrated. The VECM was used for determining the sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…In 2019, the short-term downward indicators to the left suggest that NE leads to FDI. These findings are consistent with a study conducted in Bangladesh [ 48 ], which demonstrated a positive unidirectional impact of NE on FDI using the VECM model. Additionally, in 2020, there is a bidirectional relationship between FDI and NE with high frequency.…”
Section: Empirical Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In 2019, the short-term downward indicators to the left suggest that NE leads to FDI. These findings are consistent with a study conducted in Bangladesh [ 48 ], which demonstrated a positive unidirectional impact of NE on FDI using the VECM model. Additionally, in 2020, there is a bidirectional relationship between FDI and NE with high frequency.…”
Section: Empirical Results and Discussionsupporting
confidence: 92%
“…In 2019, the short-term downward indicators to the left suggest that NE leads to FDI. These findings are consistent with a study conducted in Bangladesh [48], which demonstrated a positive unidirectional impact of NE on…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Foreign Direct Investment (FDI) has been regarded as a source of external finance to supplement domestic capital formation in the host country that can not only bring financial resources but also transmit technological knowhow, create employment opportunities, upgrade managerial skills, and increase competitiveness in the host country (Epaphra et al, 2017;Babatunde & Zhao, 2007;Afolabi et al, 2022;Kitole & Utouh, 2023;Ahmed et al, 2023;. Tanzania's exports face several challenges, including but not limited to failure to meet the international quality standard, failure to compete, lack of information on the availability of preferential markets, the existence of non-tariff barriers, especially along the border, a lack of commitment or will by some private sector to meet the demands of specified markets, a higher cost of doing business, a lack of cold chain and storage facilities at the port and airports for the storage of manufactured and horticultural goods, a lack of e-commerce skills and platforms, and the onset of the COVID-19 pandemic (National Five Year Development Plan [NFYDP], 2021; Tile et al, 2023) This study is imperative due to the fact that it specifically focuses on the trend of Tanzania's export performance from 1992 to 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, a large number of studies [ 19 , 20 , 14 , 21 , [22] , [23] , [24] , [25] , 26 , [1] , [16] , [27] , 28 , 17 , 29 , 30 , 31 , [32] , [33] , [34] , 18 , 7 , 35 , 36 , 37 ] have explored the relationship between FDI and host country's economic growth by using time series data. Some studies [ 17 , 34 , 7 ]; Cambazoglu and Karaalp, 2014 [ 22 , 24 , 31 ]; have found positive relationship, whereas, some other studies [ 27 ] have documented negative relationship.…”
Section: Introductionmentioning
confidence: 99%